Working with interpreters: how student behavior affects quality of patient interaction when using interpreters - Cha-Chi Fung; Regina Richter Lagha; Paula Henderson; Arthur G. Gomez (Medical Education Online, 2010)
Background: Despite the prevalence of medical interpreting in the clinical environment, few medical professionals receive training in best practices when using an interpreter. We designed and implemented an educational workshop on using interpreters as part of the cultural competency curriculum for second year medical students (MSIIs) at David Geffen School of Medicine at UCLA. The purpose of this study is two-fold: first, to evaluate the effectiveness of the workshop and second, if deficiencies are found, to investigate whether the deficiencies affected the quality of the patient encounter when using an interpreter. Methods: A total of 152 MSIIs completed the 3-hour workshop and a 1-station objective-structured clinical examination, 8 weeks later to assess skills. Descriptive statistics and independent sample t-tests were used to assess workshop effectiveness. Results: Based on a passing score of 70%, 39.4% of the class failed. Two skills seemed particularly problematic: assuring confidentiality (missed by 50%) and positioning the interpreter (missed by 70%). While addressing confidentiality did not have a significant impact on standardized patient satisfaction, interpreter position did. Conclusion: Instructing the interpreter to sit behind the patient helps sustain eye contact between clinician and patient, while assuring confidentiality is a tenet of quality clinical encounters. Teaching students and faculty to emphasize both is warranted to improve cross-language clinical encounters.